Towards understanding the role of forests in rural livelihoods - Campbell, Bruce M.; Luckert, M.K. (Routledge, 2002)
To understand the role of forest products in households people need to understand the nature of rural livelihoods and the characteristics of forest products. Rural households typically have a wide livelihood portfolio, encompassing a range of activities. They also generally face low availability of capital, are prone to risks and have little formal education. Many forest products are common pool resources, with some showing very little exclusivity. Many of them can be brought into a marketing chain with minimum capital investment. In the face of risk, forest products are often a source of sustenance or can be used to raise cash in the case of emergencies. Most forest products do not require high skill levels to bring them into production. There is thus a strong match between the characteristics of the rural poor and the characteristics of forest products. While this book is focussed on households, it is always necessary to see the household within the broader framework, of national policies, of a specific macro-economic framework, of international tourist markets, of a global climate, etc. The book is directed to non-economists working in the context of developing countries. The purpose is to provide an overview of methods that may be used to assess the economic importance of forests to household livelihoods. The methods are presented with a number of examples of their use, most of them drawn from developing countries. There is a danger that the numbers derived by valuation become ends in themselves. A valuation exercise is only one part of a much broader understanding that is required. The authors stress the need to understand the complexity inherent in rural livelihood strategies, to fully understand the context of particular case studies, and to use valuation only as one step towards understanding decision-making within rural households.